Prolactinoma with apoplexy in the context of thrombocytopaenia: A case report. (June 2022) - Chow, Oliver; Pham, Therese; He, Brandon; Hort, Amy; Gibson, Damien; Olsson, Gemma
Abstract: Introduction and importance: Pituitary apoplexy is a clinical syndrome that occurs secondary to abrupt haemorrhage or infarction and can cause a presentation with headache, visual disturbances, and various neurological deficits. Pituitary apoplexy is a rare clinical syndrome that is often misdiagnosed or discovered late in its clinical course due to its relatively nonspecific clinical presentation. Case presentation: The case describes patient with a giant prolactinoma which developed haemorrhagic progression in the context of previously undiagnosed coagulopathy from idiopathic thrombocytopaenia. Transcranial (rather than transnasal) surgery was performed for evacuation and debulking. Conclusion: The case highlights the management of an exceedingly large adenoma in the context of coagulopathy contributing to rapid clinical progression, as well as a positive clinical outcome in a patient with restored vision and pituitary function. Highlights: Apoplexy is a rare-sight threatening condition that must be considered in the context of undiagnosed endocrine deficiencies. A transcranial approach may be required over trans-nasal in the context of massive pituitary tumours. Early evacuation of haemorrhage allows for medical management of pituitary adenoma with good patient outcomes.